Efficacy of Physiotherapy in Plantaris Fasciitis for Inconclusive Results Demands Further Investigation: Khasiat Fisioterapi pada Fasciitis Plantaris untuk Hasil yang Tidak Meyakinkan Menuntut Penyelidikan Lebih Lanjut - Herista Novia Widanti; Hafidatul Jannah (Universitas Muhammadiyah Sidoarjo, 2024)
Plantar fasciitis patients often undergo physiotherapy interventions like gait training exercises with inner sole support to enhance functional ability. However, the efficacy of these additional interventions remains unclear. This quasi-experimental study aimed to assess the impact of such interventions on functional ability. Eight patients were divided into treatment and control groups. After a month of intervention, no significant difference was found in functional ability between the groups. While the study suggests some potential benefit, further research is needed to confirm the effectiveness of these interventions. Highlight: Evaluated physiotherapy on plantar fasciitis functional ability, with eight patients. No significant difference found after a month of intervention. Further research needed to confirm effectiveness of physiotherapy interventions. Keyword: Plantar fasciitis, physiotherapy, gait training, inner sole support, functional ability